2019
DOI: 10.18488/journal.29.2019.62.203.209
|View full text |Cite
|
Sign up to set email alerts
|

Exchange Rate Volatility, Foreign Exchange Market Intervention and Asymmetric Preferences

Abstract: Article History KeywordsAsymmetric preferences Foreign exchange market Intervention Emerging markets Exchange rate volatility Optimal reaction function GMM. JEL Classification:E58; E61; F31; G15.Policymakers in emerging market economies intervene in currency markets to counter appreciation or depreciation pressure, while also responding to the degree of exchange rate volatility. This paper investigates whether the asymmetric response in terms of foreign exchange intervention depends on the degree of exchange r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The influential work of Barajas et al (2011) notes factors such as trade and financial openness, flexibility in the factor market that allows high factor mobility among sectors and remittance receipt, which performs a countercyclical function. Last, Keefe (2014) blames the fluctuation in the exchange rate to fluctuations in the credibility of policy-makers, institutional frameworks and high exchange rate pass-throughs in countries with high remittance inflows. The study convinces us that in a dollarized economy that maintains a stable supply of foreign currency, remittances will attenuate exchange rate fluctuation, providing the same effect as trade openness.…”
Section: Reps 91mentioning
confidence: 99%
“…The influential work of Barajas et al (2011) notes factors such as trade and financial openness, flexibility in the factor market that allows high factor mobility among sectors and remittance receipt, which performs a countercyclical function. Last, Keefe (2014) blames the fluctuation in the exchange rate to fluctuations in the credibility of policy-makers, institutional frameworks and high exchange rate pass-throughs in countries with high remittance inflows. The study convinces us that in a dollarized economy that maintains a stable supply of foreign currency, remittances will attenuate exchange rate fluctuation, providing the same effect as trade openness.…”
Section: Reps 91mentioning
confidence: 99%
“…Gusmanita et al [31] utilized panel data analysis and found that credit within the domestic economy had a notably adverse influence on the EMP, indicating how the expansion of domestic credit affects the increase in net capital flows. Keefe & Shadmani [32] used dynamic threshold panel methodology and Generalized Method of Moments (GMM) and findings revealed that the non-linear aversion towards appreciation holds only in scenarios below-threshold volatility. The outcome revealed that volatilities in the exchange rate influenced the degree of response from policymakers to exchange rate dynamics.…”
Section: Empirical Literaturementioning
confidence: 99%